2021
DOI: 10.1093/jamiaopen/ooab060
|View full text |Cite
|
Sign up to set email alerts
|

CONSENSUS: a Shiny application of dementia evaluation and reporting for the KU ADC longitudinal Clinical Cohort database

Abstract: Background The University of Kansas Alzheimer’s Disease Center (KU ADC) maintains several large databases to track participant recruitment, enrollment, and capture various research-related activities. It is challenging to manage and coordinate all the research-related activities. One of the crucial activities involves generating a consensus diagnosis and communicating with participants and their primary care providers. Process … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Considering that the use of dashboards for an Alzheimer Plan is not documented in the scientific literature, future research should focus on the adoption of this tool in different regional health organizations in Quebec and at the governmental level. Studies on the use of dashboards exist for the evaluation of major neurocognitive disorders and the improvement of care offered to these individuals [20][21][22], but no study specifically mentions the use of a dashboard for an Alzheimer Plan. This will facilitate the transition from an experimental dashboard to a regular tool for managing or monitoring the implementation of an Alzheimer Plan.…”
Section: Future Work and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the use of dashboards for an Alzheimer Plan is not documented in the scientific literature, future research should focus on the adoption of this tool in different regional health organizations in Quebec and at the governmental level. Studies on the use of dashboards exist for the evaluation of major neurocognitive disorders and the improvement of care offered to these individuals [20][21][22], but no study specifically mentions the use of a dashboard for an Alzheimer Plan. This will facilitate the transition from an experimental dashboard to a regular tool for managing or monitoring the implementation of an Alzheimer Plan.…”
Section: Future Work and Recommendationsmentioning
confidence: 99%
“…The use of a dashboard in national programs such as an Alzheimer Plan further increases the need for considering the multiplicity of uses, as these dashboards need to take into consideration regional differences, especially with respect to resources and populations. Dashboards have been used in the implementation of national programs for health improvement in many countries, including the United States, Canada, and Australia [ 17 - 19 ], for evaluating major neurocognitive disorders [ 20 , 21 ] or for improving care for these individuals [ 22 ]. To our knowledge, no study has reported the use of dashboards in the context of implementing an Alzheimer Plan.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a dashboard in national programs such as an Alzheimer Plan further increases the need for considering the multiplicity of uses, as these dashboards need to take into consideration regional differences, especially with respect to resources and populations. Dashboards have been used in the implementation of national programs for health improvement in many countries, including the United States, Canada, and Australia [17][18][19], for evaluating major neurocognitive disorders [20,21] or for improving care for these individuals [22]. To our knowledge, no study has reported the use of dashboards in the context of implementing an Alzheimer Plan.…”
Section: Introductionmentioning
confidence: 99%